Low Temperature Gasification of Coconut Shell with CO2 and KOH: Effects of Temperature, Chemical Loading, and Introduced Carbonization Step on the Properties of Syngas and Porous Carbon Product - Natthaya Punsuwan; Chaiyot Tangsathitkulchai; Takayuki Takarada (International Journal of Chemical Engineering)
Effect of KOH, reaction temperature and time, and introduced carbonization step on the amount and composition of syngas as well as porous properties of the carbon products for CO2 gasification of coconut shell at low temperatures (300–700°C) was investigated. Results showed that the presence of potassium hydroxide and gasification temperature had a significant effect on the amount and composition of syngas product and facilitated the rate of hydrogen and carbon monoxide formation. It was also found that carbonization step could promote the generation of hydrogen gas as well as increasing the gas heating value per kg of gas. Furthermore, the porosity development of carbon product was found to be influenced by the chemical ratio and gasification temperature. The optimal conditions for achieving high hydrogen composition and specific surface area were to gasify coconut shell under CO2 at 600°C for 60 min with carbonization step and with chemical weight ratio of 3.0. This condition gave the hydrogen composition as high as 29.70 %weight of produced syngas with heating value of 41.4 MJ/kg of gas and specific surface area of 2650 m2/g of the carbon product.